Buoyancy-Driven Flow in Fluid-Saturated Porous Media near a Bounding Surface - Sakamoto, Hitoshi; Kulacki, Francis A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This Brief reports on heat transfer from a solid boundary in a saturated porous medium. Experiments reveal overall heat transfer laws when the flow along the wall is driven by buoyancy produced by large temperature differences, and mathematical analysis using advanced volume-averaging techniques produce estimates of how heat is dispersed in the porous zone. Engineers, hydrologists and geophysicists will find the results valuable for validation of laboratory and field tests, as well as testing their models of dispersion of heat and mass in saturated media. .
Keywords: Mechanical Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Hydrology/Water Resources; Geophysics/Geodesy.; Surface and Interface Science, Thin Films